Time-resolved in situ X-ray diffraction reveals metal-dependent metal-organic framework formation. - Wu, Y; Henke, S; Kieslich, G; Schwedler, I; Yang, M; Fraser, D; O'Hare, D (Wiley, 2016)
Versatility in metal substitution is one of the key aspects of metal-organic framework (MOF) chemistry, allowing properties to be tuned in a rational way. As a result, it important to understand why MOF syntheses involving different metals arrive at or fail to produce the same topological outcome. Frequently, conditions are tuned by trial-and-error to make MOFs with different metal species. We ask: is it possible to adjust synthetic conditions in a systematic way in order to design routes to desired phases? We have used in situ X-ray powder diffraction to study the solvothermal formation of isostructural M2 (bdc)2 dabco (M=Zn, Co, Ni) pillared-paddlewheel MOFs in real time. The metal ion strongly influences both kinetics and intermediates observed, leading in some cases to multiphase reaction profiles of unprecedented complexity. The standard models used for MOF crystallization break down in these cases; we show that a simple kinetic model describes the data and provides important chemical insights on phase selection.